Effect of educational intervention based on protection motivation theory on preventive behaviors of respiratory infections among hospital staff - Rakhshani, Tayebeh; Nikeghbal, Sepahdar; Kashfi, Seyyed Mansour; Kamyab, Amirhossein; Harsini, Pooyan Afzali; Jeihooni, Ali Khani (Frontiers in Public Health, 2024)
Background Hospital staff represent a vulnerable population for respiratory diseases. Consequently, the implementation of training programs becomes imperative as a preventive measure against such infections in these populations. The current study was conducted to examine the impact of an educational intervention based on the Protection Motivation Theory (PMT) on preventive behaviors for respiratory infections among a group of hospital staff. Methods This experimental study involves a sample of 150 hospital staff from Gachsaran City, Iran, in 2021–2022. The sampling technique involved the utilization of a random assignment approach to allocate individuals into two distinct groups: the experimental group, consisting of 75 participants, and the control group, also including 75 individuals. The data collection instrument was a questionnaire designed in accordance with the PMT. This questionnaire was administered to both the experimental and control groups prior to the intervention as well as two months following the intervention. The intervention program consisted of a total of five sessions, each lasting for 60 min, for the experimental group. These sessions were conducted on a weekly basis over a period of two and a half months. Specifically, there were two sessions held every month and one session held every two weeks. Following the completion of the program, the data was entered into SPSS-24 statistical software for analysis using paired t-tests, independent t-tests, and chi-square tests. Results The results indicated that prior to the intervention, there was no significant difference between the two groups in terms of perceived vulnerability constructs (p = 0.25), perceived severity (p = 0.63), perceived response (p = 0.32), and perceived reward (p = 0.11). Besides, there was no considerable distinction in perceived self-efficacy (p = 0.84), perceived response cost (p = 0.33), fear (p = 0.45), behavior motivation (p = 0.51), knowledge (p = 92), or vaccination behavior (p = 0.12) before the educational intervention. However, a significant change was noticed in each of the mentioned variables between the two groups after the intervention (p < 0.05). Conclusion The results of this study indicated that the implementation of an educational intervention grounded in the PMT yields positive outcomes in enhancing preventative behaviors pertaining to respiratory infections. Hence, it is recommended to utilize an intervention grounded in this theory among hospital staff as a viable approach to mitigating the occurrence of respiratory infections.